Diksi dan Gaya Bahasa dalam Ceramah Ustadz Abdul Somad di Madura - Julherman (Indonesian Journal of Applied Linguistics Review, 2022)
The purpose of this study is to explain the rhetorical style of preaching by Ustadz Abdul Somad and the consequences when delivering his lecture at the Al-Hamidy Islamic Boarding School, Banyuanyar, Pamekasan. This study uses a qualitative method that is descriptive analysis. The data collection technique is Download, view, listen, and record. As for the data analysis technique, using Aristotle's rhetorical theory, namely the five canons of rhetorics combined with Gorys Keraf's concepts, namely diction and language style, characterized by (1) Reading every lecture discourse that has been converted into written language; (2) Marking utterances that contain diction and figurative language; (3) Identifying diction characteristics (intonation, high tone, low tone, connotative, formal, informal, idiom, slang, and jargon), language style characteristics (majas, metaphor, lexicon, etc.), body style characteristics (looking to the left/ right, swinging arms, looking down). The results showed that Ustadz Abdul Somad combined diction and language style including (words and word choice, word meaning, language style based on word choice, tone, sentence structure, meaning, gestures).